Effects of Different Acetic Acid Immersion Time on the Properties of Collagen from Pangasius Skin - Clara Amelia Kusumawinahyu; Sharilla Aryananti Abidin; Patmawati; Dwi Yuli Pudjiastuti; Dwitha Nirmala; Mochammad Amin Alamsjah; Laksmi Sulmartiwi; Raseetha Vani Siva Manikam (Jurnal Ilmiah Perikanan dan Kelautan, 2022)
Highlight Research Experimental use of pre-treated pangasius skin as collagen raw material using different acetic acid immersion time Effects of immersion time on the yield of collagen from pangasius skin Effects of immersion time on the proximate content of collagen from pangasius skin Presenting SDS-Page profile of collagen from pangasius skin   Abstract Pangasius sp. production in Indonesia has reached 384,310 tons in 2019. One of the main waste in pangasius fillet industry is the skin, which reached to 6% of body mass. Fish skins are alternative for making collagen because it has no restrictions for certain religions and ethnicities. Collagen is a protein biomaterial which acts as the main component of connective tissue. Extracting collagen using organic acids such as acetic acid is the most common extraction method. Herein, we report the effects of different immersion time of acetic acid to collagen properties from pangasius skin. In this study, pangasius skin was treated using 10% alcohol with the ratio 1:10 (w/v) for defatting and 0.1M NaOH with the ratio 1:10 (w/v) for eliminating non-collagenous protein. The immersion of 0.5M acetic acid was carried out on pangasius skin with the ratio of 1:20 (w/v), for 24, 48, and 72h at temperature less than 15oC. The sample was salted-out for 24 hours with NaCl until the concentration reached 2.5M, then the sample was freeze-dried at -40oC. This study investigated that longer immersion time affected the properties of pangasius skin collagen. Different immersion time significantly affected the yield of collagen from pangasius skin (p<0.05). Pangasius skin has a potential to be used as collagen raw material, and 72h of immersion time (P3) is suggested to produce pangasius skin collagen with the highest yield and protein content (6.15 % and 9.26 %). Production of collagen from the fish skin will contribute to increase pangasius waste valorization in pharmaceutical industry.